Use of Tooth Clearing Technique to Determine Root and Canal Morphology of Permanent Maxillary Third Molars in Population of Peshawar: An in Vitro Cross-Sectional Study (Medical Forum Monthly, 2024)
Objective: To use tooth clearing procedure to determine the number of roots, canals and canal configuration in permanent maxillary third molars.Study Design: Cross- sectionalPlace and Duration of Study: This study was conducted at the Surgery departments of three dental colleges of Peshawar, from 4th November 2022 to 3rd May 2023.Methods: 193 maxillary third molars (MTM) were extracted from both genders, with fully developed roots. Following collection, the number of roots were visually assessed and cavity was prepared, the pulp was cleaned and canals were stained with Indian ink. Teeth were dehydrated in increasing alcohol concentrations after decalcification for five days in nitric acid. Teeth were completely transparent after being immersed in methyl-salicylate for 72 hours. Transparent teeth's root and canal numbers were recorded.Results: Among 193 extracted MTM’s, (54.9%) had three, (25.9%) single and (15.5%) had two roots. Three root canals (46.6%), followed by two (22.3%), one (18.1%) and four (13 %) canals respectively. The predominant canal configuration in mesiobuccal (64.7%), distobuccal (100%) and palatal root (98%) was Type I respectively in the three separate root specimen. For the three fused root form, Type VIII (70.9%) was the frequent configuration. There was no significant correlation between the maxillary third molar’s root canal count and number of roots.Conclusion: Three roots and three canals were the common patterns for maxillary third molars. Vertucci’s Type 1 canal configuration was the predominant form.